Evaluation of the constituent compounds, antioxidant, anticancer, and antimicrobial potential of Prangos ferulacea plant extract and its effect on Listeria monocytogenes virulence gene expression - Jalil Sarghaleh, Shahab; Alizadeh Behbahani, Behrooz; Hojjati, Mohammad; Vasiee, Alireza; Noshad, Mohammad (Frontiers in Microbiology, 2023)
Prangos ferulacea plant is very popular in Iran due to its unique properties in treating diseases and its special flavor. In order to check the characteristics of this plant, first its extract was extracted using maceration method. Its chemical composition was investigated using high performance liquid chromatography (HPLC), that p-coumaric was identified as its main compound, and Fourier-transform infrared spectroscopy (FTIR) showed the presence of functional groups related to phenolic, flavonoid, tannins, carboxylic acids such as caffeic acid and coumaric acid composition. The content of total phenol (TPC), total flavonoid (TFC), and beta-carotene were equal to 202.04±5.46 mg gallic acid equivalent (GAE)/g dry weight, 1909.46±13 µg quercetin (QE)/g of dry weight, and 2.91 mg/100 g. The antioxidant property of the extract was evaluated using 2,2-Diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-azino-bis(3-ethylbenzothiazoline-6sulphonic acid (ABTS) free radical scavenging and ferric reducing antioxidant power assay (FRAP). According to the IC50 obtained for DDPH (274±7.2 μg/mL) and ABTS (120.45±9.6 μg/mL) and FRAP values (1.92±0.05 μg ascorbic acid equivalent (AAE)/g of extract), this extract had high antioxidant properties. Cytotoxicity was evaluated against the survival of HT 29 cells, that IC50 was 82.15 ± 0.02 µg/mL. The antimicrobial property of the extract was calculated using disk diffusion agar (DDA), well diffusion agar (WDA), minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). Listeria monocytogenes has the highest sensitivity to this extract and inhibition zone based on DDA and WDA method and with an MIC and MBC equal to 16 mg/mL and 128 mg/mL has the least resistant. Morphology change of L. monocytogenes strain was proved through scanning electron microscope (SEM) and confocal laser scanning microscopy (CLSM). The extract caused a significant reduction in the transcription of genes involved in film formation ability of L. monocytogenes. The obtained results fully prove the very practical and pragmatic characteristics of P. ferulacea.